A descriptive investigation of clinical practice models used by cardiovascular genetic counselors in North America. Issue 2 (12th October 2022) - Rickman, Allison F.; Fitzgerald‐Butt, Sara M.; Spoonamore, Katherine G.; Ware, Stephanie M.; Helm, Benjamin M.
Abstract: Cardiovascular genetic counseling has expanded as an established genetic counseling specialty over the last 20 years. Despite guidelines recommending genetic counseling for heritable cardiac diseases, there have been limited descriptions of the practice model types used for different clinical indications seen in this genetic counseling subspecialty. We aimed to describe current clinical practice models used by cardiovascular genetic counselors and to document practice model strengths, challenges, and areas for improvement. Genetic counselor respondents ( n  = 63) who self‐reported seeing cardiovascular indications were recruited through the National Society of Genetic Counselors and Twitter. They completed a survey describing the types of healthcare professionals with whom they collaborate to see common cardiovascular indications, the nature of their collaboration, and their qualitative experiences with their practice models. Clinical indications addressed in this survey were hypertrophic cardiomyopathy, dilated cardiomyopathy, all other cardiomyopathies, arrhythmias, aortopathies, dyslipidemias, pulmonary arterial hypertension, and congenital heart defects. Data were analyzed using descriptive statistics and thematic analysis. We found that the composition of multidisciplinary provider practice models varies by indication, though general cardiologists were the most common collaborative provider reported. Practice models including geneticists were most common for aortopathy indications. Overall, the majority of respondents were satisfied with the practice models they reported. While a wide variety of successes, challenges, and areas for improvement of practice models were reported, collaboration, communication, and access to appropriate providers for patient care were consistent themes across these three questions. To our knowledge, this is the first description of practice models used by cardiovascular genetic counselors. The results of this study add to the knowledge of this specialty of genetic counseling and assist in understanding the needs and challenges for developing cardiovascular genetics programs and clinics.